FRI0721-HPR We are in it together: exploring rheumatology practice with patients as researcher partners. (12th June 2018) - Gjønnes Tvedten, O.; Croker, J.; Croker, A.; Perry, N.; Williams, K.; Lawrence, M.
Abstract : Background: Rheumatological conditions are often complex requiring careful history-taking, discussion of options, and plans for treatment and ongoing monitoring. Accordingly, similar to many areas in health, the importance of good communication with patients and with colleagues is well recognised. Issues such as adherence, safety, patient satisfaction and workplace thriving are often cited as supporting evidence for good communication. However communication comes with different intentions (e.g. developed as a one-size-fits-all or personalised to individual situations), in different forms (e.g. verbal, non-verbal, written), occurs within and across different spaces (e.g. face-to-face and technologically enabled) and uses time in different ways (e.g. synchronous and asynchronous, structured or unstructured) 1 . While the literature relating to colleague communication is vast, covering different aspects of communication, literature relating to patient communication tends to focus on one-size-fits-all styles of written communication, such as web resources and printed patient handouts, and verbal and non-verbal communication styles during consultations. We identified scope to contribute to understandings about patient communication by focusing on personalised written communication for patients, as both a product of the consultation and a tool for ongoing dialogue. In taking a patient-centred approach we sought to involve patients as co-researchers and dialogue partners. Together we explored the value of patients' personalised written consultation summaries. Objectives: The purpose was to (i) to enhance patient communication within a rheumatology practice, and (ii) to develop insights into collaborating with patients in research. Methods: Collaborative dialogical inquiry provided an appropriate research method for exploring the complex practice of communication, transforming such practice and being authentic to the topic by involving patients. The research team was composed of a rheumatologist, a practice nurse, a medical registrar, a researcher and two patients. Using a lens of appreciative inquiry, data were collected through documenting and recording formal and informal discussions between co-researchers, observing practice and undertaking semi-structured interviews with 20 patients. Each researcher kept a reflective journal about their experiences. Data and experiences were iteratively analysed and discussed to identify and further explore themes. Results: The personalised written consultation summary was interpreted to be a living document, shared document, valued document, dialogued document and stored document. Our research experiences echoed these themes, in that they were lived, shared, valued, dialogued and recorded . The five themes, and their echoes, will be illustrated with quotes. Implications for patient-centred practice and research will be discussed. Conclusions: A set of reflective questions will be posed for the consideration of patients, their families and carers and their clinicians, as well as researchers. These questions have scope to inform dialogue about patient-centred communication in rheumatology practice, and guide collaborative research in this space. Reference: 1. Croker, Higgs, Trede. Collaborating in healthcare2016. Sense Publishers, Rotterdam. Disclosure of Interest: None declared